Peranan Cerita Rakyat Dalam Mempromosikan Daya Tarik Wisata Melalui Storytelling - Suyasa, I Made; Anggratyas, Putu Arya Reksa (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2025)
This study aims to analyze the strategic role of folklore as an instrument in promoting tourism destinations through storytelling approaches within the framework of Cultural Tourism Communication. Tourism destinations are increasingly selling not merely natural beauty or infrastructure, but also profound "experiences" and "meanings," where folklore serves as the soul of a place. This research employs a qualitative method with a literature review approach, collecting data from secondary sources including books, journal articles, and scholarly publications related to cultural tourism, folklore, and communication. The analysis applies Cultural Tourism Communication theory, which emphasizes the exchange of meanings and cultural values between tourists and local communities. This theoretical framework is reinforced by the concept of storytelling as an effective communication medium for transmitting values. Folklore is not viewed as a passive narrative, but as a "living culture" revitalized through performances by tour guides or digital media, thereby creating emotional connections and profound experiential tourism for visitors. Findings indicate that integrating folklore through storytelling plays a crucial role in: (1) destination differentiation, distinguishing destinations through unique cultural narratives; (2) cultural preservation, reviving nearly extinct oral traditions; (3) enhancing tourism experiences by adding layers of meaning and context to tourist attractions; and (4) destination branding, shaping authentic and distinctive perceptions. This study concludes that folklore-based storytelling constitutes a powerful cultural tourism communication strategy. It functions not only as a promotional tool, but also as a bridge connecting the past with the present, tourists with local communities, while preserving intangible cultural heritage for sustainable tourism development.